2019
DOI: 10.1007/s00162-019-00493-z
|View full text |Cite
|
Sign up to set email alerts
|

Detecting exotic wakes with hydrodynamic sensors

Abstract: Wake sensing for bioinspired robotic swimmers has been the focus of much investigation owing to its relevance to locomotion control, especially in the context of schooling and target following. Many successful wake sensing strategies have been devised based on models of von Kármán-type wakes; however, such wake sensing technologies are invalid in the context of exotic wake types that commonly arise in swimming locomotion. Indeed, exotic wakes can exhibit markedly different dynamics, and so must be modeled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Recently, Colvert et al (2018) investigated the classification of wake topology (e.g., 2S, 2P+2S, 2P+4S) behind a pitching airfoil from local vorticity measurements using neural networks; extensions have compared performance for various types of sensors (Alsalman et al 2018). In Wang & Hemati (2017) the k nearest neighbors (KNN) algorithm was used to detect exotic wakes. Similarly, neural networks have been combined with dynamical systems models to detect flow disturbances and estimate their parameters (Hou et al 2019).…”
Section: Flow Snapshots Pod Modesmentioning
confidence: 99%
“…Recently, Colvert et al (2018) investigated the classification of wake topology (e.g., 2S, 2P+2S, 2P+4S) behind a pitching airfoil from local vorticity measurements using neural networks; extensions have compared performance for various types of sensors (Alsalman et al 2018). In Wang & Hemati (2017) the k nearest neighbors (KNN) algorithm was used to detect exotic wakes. Similarly, neural networks have been combined with dynamical systems models to detect flow disturbances and estimate their parameters (Hou et al 2019).…”
Section: Flow Snapshots Pod Modesmentioning
confidence: 99%
“…After constructing the library, we use a supervised learning strategy to classify an unknown wake by comparing its hydrodynamic signals with the entries in the library. The synthesis of this protocol is following our previous work, 4 which is summarized graphically in Fig. 1.…”
Section: Wake Classification Protocolmentioning
confidence: 99%
“…In our previous work, we showed that this feature vector provided a convenient and relatively robust summary of the time-series signature imparted by various idealized wakes in our flow model. 4 In that study, we used the fast Fourier transform to extract the frequency content of the time-domain signal from each of the r wake realizations used to build-up the library {V 1 , V 2 , . .…”
Section: Wake Classification Protocolmentioning
confidence: 99%
See 2 more Smart Citations